UPAYA MENINGKATKAN HASIL BELAJAR PKN MATERI MAKNA HAK DAN KEWAJIBAN WARGA NEGARA MELALUI MODEL INQURY BASED LEARNING (IBL) TIPE MAKE A MATCH - Rahmatsyah Rahmatsyah (Jurnal Sains Riset, 2022)
This study aims to determine the efforts to improve learning outcomes of Civics on the meaning of the rights and obligations of citizens through the make a match type of inquiry-based learning (iBL) model for students of Class XII MIPA 1 SMA Negeri 2 Sigli Pidie in the 2021/2022 academic year. The subjects of this study were students of class XII MIPA 1 SMA Negeri 2 Sigli for the academic year 2021/2022, totaling 18 students, to obtain data the authors used to test and non-test techniques. After the data is collected, the writer processes and analyzes the data by comparing the results of observations and tests in cycle I and cycle II. The application of the Make A Match Inquiry-Based Learning (IBL) model can improve learning outcomes for civic education subjects, especially the meaning of citizens' rights and obligations for students of class XII MIPA 1 SMA Negeri 2 Sigli semester 1 for the 2021/2022 academic year. The increase in the average value is 55.6 in the initial conditions to 74.7 in the first cycle and becomes 85.8 in the second cycle. The average value of the first cycle increased by 19.2% from the initial conditions, and the average value of the second cycle increased by 711.4% from the first cycle. The increase in the overall average value of the class was 30.3%. While learning completeness in the first cycle there was an increase of 44.5% from the initial condition, the second cycle increased by 34% from the first cycle. The overall improvement incompleteness was 78%Keywords: Learning outcomes, Inquiry-Based Learning (IBL) model Make A Match type, and the meaning of citizens' rights and obligations.